P2 type layered positive electrode material with high voltage and high pseudocapacitance ratio and solid sodium battery thereof

A P2-type layered cathode material co-doped with Li, Ca, and Ti elements addresses the limitations of existing solid-state sodium batteries by providing high voltage and pseudocapacitance, enhancing performance in both liquid and solid-state sodium batteries.

CN119191379AActive Publication Date: 2024-12-27FUJIAN NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411234454.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

Current solid-state sodium batteries face challenges in achieving high energy density and high operating voltage, with materials like NaCrO2 and Na3V2(PO4)3 exhibiting limited performance.

Method used

A P2-type layered cathode material co-doped with Li, Ca, and Ti elements is synthesized through a simple solid phase method, resulting in a material with high voltage and pseudocapacitance ratio, which is integrated into both liquid and solid-state sodium batteries.

Benefits of technology

The co-doped P2-type layered cathode material exhibits excellent rate and cycle performance in liquid batteries and enhanced structural stability in solid-state batteries, maintaining high capacity and stability over multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191379A_ABST
    Figure CN119191379A_ABST
Patent Text Reader

Abstract

The invention discloses a P2 type layered positive electrode material with high voltage and high pseudocapacitance ratio and a solid sodium battery thereof. The preparation method comprises the following steps: respectively adding required amounts of Na2CO3, Li2CO3, NiO, Mn2O3, CaO and TiO2 into a ball-milling tank according to a chemical formula, putting ball-milling beads into the ball-milling tank, carrying out ball-milling by using a ball mill to obtain powder, pressing the ball-milled powder into pellets, putting the pellets into a muffle furnace, and calcining to obtain the positive electrode material Na < 0.68 > Li < 0.10 > Ni < 0.25 > Mn < 0.63 > Ca < 0.01 > Ti < 0.01 > O2. According to the invention, a simple solid phase method is adopted to carry out Li, Ca and Ti element co-doping on a typical P2 type sodium battery positive electrode material Na < 0.68 > Ni < 0.25 > Mn < 0.75 > O < 2 >, and the P2-Na < 0.68 > Li < 0.10 > Ni < 0.25 > Mn < 0.63 > Ca < 0.01 > Ti < 0.01 > O < 2 > layered positive electrode material which is resistant to high voltage and high in pseudocapacitance ratio is obtained. The particle surface of the material is smoother, and the material has ultrahigh pseudocapacitance, so that the material shows excellent rate and cycle performance in a liquid battery. Meanwhile, the solid-state sodium battery is prepared from the material, the material shows more stable cycle performance than a liquid-state battery, and the material is found to have better structural stability in the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery materials, and specifically relates to a P2-type layered positive electrode material with high voltage and high pseudocapacitance ratio and a solid-state sodium battery thereof. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries (SIBs) are considered to be low-cost and more sustainable devices. At the same time, solid-state sodium batteries (SSBs) have the advantages of high energy density and good safety, which can effectively overcome the key challenges of relatively low energy and cycle life. Compared with traditional organic liquid electrolytes, solid electrolytes not only improve safety, but also inhibit the growth of Na dendrites during the cycle, thereby improving the cycle stability. Most solid-state sodium battery studies use NaCrO2 or Na3V2(PO4)3 as cathodes, mainly due to their low operating voltage and excellent rate performance, which match various solid electrolytes. However, both materials have the problems of limited energy density and low operating voltage (most of the currently reported voltages are less than 4.0 V). Therefore, the development of SSBs with high energy density and high operating voltage remains a huge challenge, and the development of SSBs is urgently needed. Summary of the invention

[0003] The object of the present invention is to provide a P2-type layered positive electrode material with high voltage and high pseudocapacitance ratio and a solid-state sodium battery thereof.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A high-voltage, high-pseudocapacitance P2-type layered cathode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 The method for preparing O2 comprises the following steps: 1) According to the chemical formula, add appropriate amounts of Na2CO3, Li2CO3, NiO, Mn2O3, CaO, and TiO2 into the ball mill, add appropriate amounts of ball mill beads, and use a rotation speed of 900-1100 r min -1 Ball mill for 0.4-0.6 h to obtain powder; 2) The ball-milled powder was pressed into pellets at 7.5-8.5 MPa and placed in a muffle furnace at 4.5-5.5°C min -1 After the heating rate was raised to 900-1000 °C and calcined for 11-13 h, the P2-type layered cathode material Na with high voltage and high pseudocapacitance ratio was obtained. 0.68 Li 0.10 Ni 0.25 Mn0.63 Ca 0.01 Ti 0.01 O2(NM-L10CT).

[0005] The positive electrode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 Application of O2 in sodium ion batteries: (1) Liquid battery assembly: The positive electrode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2, polyvinylidene fluoride (PVDF) and carbon black conductive agent (SP) were mixed and ground according to a mass ratio of 8:1:1 and then evenly coated on a 1 cm 2 The positive electrode was carbon-coated aluminum foil, the negative electrode was metallic sodium, and the electrolyte was 0.8 M NaClO4 in propylene carbonate (PC) solvent (fluoroethylene carbonate (FEC) was an additive).

[0006] (2) Solid-state battery assembly: using Na3Zr2Si2PO 12 (NZSP) is a solid electrolyte with Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2 is used as the positive electrode and metallic sodium is used as the negative electrode to assemble the NM-L10CT / NZSP / Na solid-state sodium battery. The battery assembly is carried out in a glove box under argon protection (oxygen and moisture content <1 ppm).

[0007] The present invention adopts the above technical solution and adopts a simple solid phase method to treat the typical P2 type sodium battery positive electrode material Na 0.68 Ni 0.25 Mn 0.75 O2 is co-doped with Li, Ca, and Ti elements to obtain a P2-Na with high voltage resistance and high pseudocapacitance ratio. 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01O2 layered positive electrode material. The particle surface of the material is smoother and has an ultra-high pseudocapacitance (>90%), thus showing excellent rate and cycle performance in liquid batteries. At the same time, the present invention also uses this material to make a solid-state sodium battery, which shows a more stable cycle performance than a liquid battery, and it is found that it has better structural stability in a solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 XRD patterns of NM and NM-L10CT materials.

[0009] Figure 2 SEM images of NM (a) and NM-L10CT (b).

[0010] Figure 3 For NM (a) and NM-L10CT (b) at 0.1 to 1.0 mV s −1 CV curves at different scan rates; Percentage of capacitance contribution and diffusion contribution of NM (c) and NM-L10CT (d) in the charge storage process at different scan rates.

[0011] Figure 4 Electrochemical performances of NM and NM-L10CT at 2.0-4.3 V: (a) 0.1 C charge-discharge curve, (b) rate curve, and (c) 1 C cycle curve.

[0012] Figure 5 Electrochemical performances of NM and NM-L10CT: 0.1 C charge-discharge curves: (a) 2.0-4.4 V, (b) 2.0-4.5 V; 1 C cycle curves: (c) 2.0-4.4 V, (d) 2.0-4.5 V.

[0013] Figure 6 Electrochemical performance of NM-L10CT / NZSP / Na solid-state sodium battery at 2.0-4.3 V: (a) 1 C charge-discharge curve of each cycle, (b) rate curve, (c) 1 C cycle curve. (d) Cycle curve of NM-LCT, (e) Cycle curve of NM-L10CT / NZSP / Na at 2.0-4.2 V.

[0014] Figure 7 XRD patterns of NM-L10CT and NM-L10CT / NZSP / Na electrodes before and after 200 cycles at 2.0-4.3 V.

[0015] Figure 8Liquid battery electrode after 200 cycles at 2.0-4.3 V: (a), (b) TEM image, (c) corresponding FFT image and solid-state battery electrode: (d), (e) TEM image, (f) corresponding FFT image. DETAILED DESCRIPTION

[0016] In the following embodiments, the typical P2 type sodium battery positive electrode material Na 0.68 Ni 0.25 Mn 0.75 O2 is abbreviated as NM, and the positive electrode material Na after NM is co-doped with Li, Ca, and Ti elements 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2 is recorded as NM-L10CT. Example

[0017] P2-type layered cathode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 Preparation method of O2: 1) According to the chemical formula, add appropriate amounts of Na2CO3, Li2CO3, NiO, Mn2O3, CaO, and TiO2 into the ball mill, add appropriate amounts of ball mill beads, and use a rotation speed of 1000 r min -1 The mixture was ball milled for 0.5 h to obtain powder; 2) The ball-milled powder was pressed into pellets at 8.0 MPa and placed in a muffle furnace at 5°C min -1 After the heating rate was raised to 900 °C and calcined for 12 h, the P2-type layered cathode material Na with high voltage and high pseudocapacitance ratio was obtained. 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2 (NM-L10CT). Example

[0018] Application of positive electrode material NM-L10CT in sodium ion batteries: (1) Liquid battery assembly: NM-L10CT, PVDF and SP were mixed and ground in a mass ratio of 8:1:1 and then evenly coated on a 1 cm 2The carbon-coated aluminum foil was used as the positive electrode, the negative electrode was metallic sodium, and the electrolyte was 0.8 M NaClO4 in PC solvent (FEC was an additive).

[0019] (2) Solid-state battery assembly: using Na3Zr2Si2PO 12 (NZSP) was used as the solid electrolyte, NM-L10CT was used as the positive electrode, and metallic sodium was used as the negative electrode to assemble the NM-L10CT / NZSP / Na solid-state sodium battery. The battery assembly was carried out in a glove box under argon protection (oxygen and moisture content <1 ppm).

[0020] Among them, Na3Zr2Si2PO 12 The preparation process of (NZSP) solid electrolyte is as follows: 1) Using the traditional solid phase method, Na2CO3, SiO2, ZrO2, and NH4H2PO4 are taken as raw materials according to the stoichiometric ratio, put into a ball mill, and use isopropanol as a grinding aid at 600 r min -1 2) After the powder is dried, it is transferred to a muffle furnace and heated at 900℃ for 10 h, and then taken out and ball-milled again. The dried powder is pressed into pellets at a pressure of 20 MPa, and sintered at 1200℃ for 15 h in a high-temperature muffle furnace to finally obtain the NZSP solid electrolyte.

[0021] Comparative Example 1 Cathode Material: Na 0.68 Ni 0.25 Mn 0.75 Application of O2 (NM) in sodium ion batteries: Liquid battery assembly: NM, PVDF and SP were mixed and ground in a mass ratio of 8:1:1 and evenly applied on a 1 cm 2 The carbon-coated aluminum foil was used as the positive electrode, the negative electrode was metallic sodium, and the electrolyte was 0.8 M NaClO4 in PC solvent (FEC was an additive).

[0022] Figure 1 The XRD diagrams of NM and NM-L10CT materials show that the space groups of these two positive electrode materials are P63 / mmc The P2-type layered structure is shown in Figure 1, and no impurity peaks appear, indicating that elements such as Li, Ca, and Ti are uniformly incorporated into the material. At the same time, after zooming in on the local XRD spectrum at 15.5°-17.0°, it is found that the (002) diffraction peak of NM-L10CT shifts to the right, indicating that the lattice parameter c-axis of the material has shrunk and its interlayer spacing has decreased.

[0023] Figure 2These are the SEM images of NM (a) and NM-L10CT (b). It can be seen that the surface of the NM material is relatively rough, and there are secondary particles on the surface, with a size of about 2-5 um, while the surface of the NM-L10CT material is smoother, and the layered morphology is more obvious, with a size of about 1-3 um.

[0024] Figure 3 The speed CV curves of NM (a) and NM-L10CT (b) at different sweep times are shown in the formula i(V) = k1v + k2v 1 / 2 Further quantitative determination of the pseudocapacitive behavior of the material shows that as the scan rate increases, the capacitance contribution also gradually increases (e.g. Figure 3 c, d), where it can be observed that the capacitance contribution of NM-L10CT exceeds 90% at any scan rate, indicating that it is a high pseudocapacitive cathode material with excellent sodium ion diffusion ability.

[0025] Depend on Figure 4 It can be seen from a that the charge and discharge curve of NM is a multi-voltage platform charge and discharge process, while the charge and discharge curve of NM-L10CT shows a solid solution charge and discharge process. In particular, NM has an ultra-long voltage platform around 4.2 V. This is mainly because the TM layer is prone to P2-O2 phase transition under deep Na removal state, and at this voltage, the ARRs reaction is triggered. Solid solution charge and discharge reduces the irreversible phase change during the charge and discharge process, and it can be clearly seen that the ARRs reaction is suppressed. Figure 4 In b, the specific capacity of NM-L10CT at 5 C and 10 C high rates increased from 66.9 mAh g of NM to 1.3 mAh g of NM-L10CT at 5 C and 10 C high rates, respectively. −1 , 49.7 mAh g −1 Increased to 102.88 mAh g −1 , 94.31 mAh g −1 At the same time, Figure 4 As can be seen from Figure c, the capacity retention rate of NM-L10CT at 1 C cycle for 200 cycles increased from 26.9% of NM to 78.9%, still showing excellent cycle stability.

[0026] Figure 5 The electrochemical performances of NM and NM-L10CT at 2.0-4.4 V and 2.0-4.5 V. Figure 5c, d, NM-L10CT has a capacity retention rate of 72.6% after 200 cycles at 1 C at 2.0-4.4 V (67.3% at 2.0-4.5 V), which is significantly better than NM’s capacity retention rate of 28.8% (24.8% at 2.0-4.5 V). Even at a high operating voltage of 2.0-4.5 V, NM-L10CT can still maintain good cycle stability, indicating that this material is also a high-voltage resistant positive electrode material.

[0027] Depend on Figure 6 It can be seen that in the voltage range of 2.0-4.3 V, the capacity at 1 C current rate is as high as 115.4 mAhg -1 , the capacity retention rate after 300 cycles is 74.2% ( Figure 6 c), significantly better than the retention rate of 58.5% of NM materials in liquid batteries ( Figure 6 d) By Figure 6 b It can be seen that the average specific capacities at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, 5 C, 10 C and 0.2 C are 120.9 mAh g -1 , 117.4 mAh g -1 , 110.5 mAh g -1 、104.0 mAh g -1 , 102.2 mAh g -1 、97.1 mAh g -1 , 74.5 mAh g -1 and 1116.2 mAh g -1 When the current density is switched from 10 C to 0.2 C, the SSBs also exhibit excellent rate performance with almost no capacity degradation (99.0% of the original capacity at 0.2 C), indicating their excellent reversibility and stable and reliable interface. The capacity retention rate after 500 cycles at 1 C at 2.0-4.2 V is still as high as 81.2% ( Figure 6 e), showing excellent long-term cycling performance.

[0028] like Figure 7 It can be seen that the electrode still maintains the P2 type structure and no phase change occurs. From the local magnification of 15.5-17°, it can be seen that the electrode diffraction peaks after cycling are shifted to low angles, indicating that the lattice parameter c becomes larger and the interlayer spacing expands. In addition, the displacement of the solid-state battery after cycling is significantly smaller than that of the liquid battery, indicating that the NZSP solid electrolyte in the solid-state system further promotes the reversibility of the NM-L10CT material.

[0029] Figure 8a, b, d, and e are TEM images of NM-L10CT material and liquid-solid electrode sheet, respectively. It can be seen from the figure that in the liquid battery system, the active material of the electrode is severely corroded, and the lattice is distorted, which seriously damages the Na + The transmission channel of the electrode is blocked, causing the capacity to decay rapidly. Compared with the solid-state battery system, it can be clearly observed that there is a uniform amorphous passivation layer of about 1.47 nm on the surface of the material, which keeps the electrode and the electrolyte in very uniform interface contact. At the same time, the layered structure of the active material in the electrode remains very intact, thus showing better electrochemical performance in the solid-state battery. Figure 8 c, f are the lattice fringes of the (004) peak of the active material in the electrode and the corresponding Fourier transform image, respectively. It can be seen that the interlayer spacing of the (004) peak of the electrode in the solid-state battery is 0.28 nm, which is slightly smaller than the interlayer spacing of the (004) peak of the liquid state of 0.30 nm, which also corresponds to Figure 7 The diffraction peak of the liquid battery shifts to a low angle. At the same time, in the Fourier transform image, it can be found that in the liquid battery system, polycrystallization gradually occurs in the single crystal structure, while in the solid system, a very complete hexagonal single crystal layered structure is still maintained.

[0030] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a P2-type layered positive electrode material with high voltage and high pseudocapacitance ratio, characterized in that: The positive electrode material is Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2, the preparation method thereof comprises the following steps: 1) According to the chemical formula, the required amounts of Na2CO3, Li2CO3, NiO, Mn2O3, CaO and TiO2 are added into a ball mill, ball mill beads are placed in the ball mill, and powder is obtained by ball milling; 2) Press the milled powder into pellets and place them in a muffle furnace at 4.5~5.5℃ min -1 After the heating rate was raised to 900-1000 °C and calcined for 11-13 h, the P2-type layered cathode material Na with high voltage and high pseudocapacitance ratio was obtained. 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2.

2. The method for preparing a P2-type layered positive electrode material with high voltage and high pseudocapacitance ratio according to claim 1, characterized in that: The speed of the ball mill is 900-1100 r min -1 , the ball milling time is 0.4~0.6 h.

3. The method for preparing a P2-type layered positive electrode material with high voltage and high pseudocapacitance ratio according to claim 1, characterized in that: The pressure for pressing the powder into pellets is 7.5~8.5 Mpa.

4. The positive electrode material Na obtained by the preparation method according to any one of claims 1 to 3 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2.

5. The positive electrode material Na as claimed in claim 4 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 Application of O2 in sodium-ion batteries.

6. The use according to claim 4, characterized in that: The positive electrode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2 is assembled into a liquid battery: the positive electrode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2, PVDF and SP were mixed and ground in a mass ratio of 8:1:1 and evenly coated on a 1 cm 2 The carbon-coated aluminum foil was used as the positive electrode, the negative electrode was metallic sodium, and the electrolyte was 0.8 M NaClO4 in propylene carbonate solvent.

7. The use according to claim 4, characterized in that: The positive electrode material Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2 assembled into solid-state batteries: using Na3Zr2Si2PO 12 As solid electrolyte, Na 0.68 Li 0.10 Ni 0.25 Mn 0.63 Ca 0.01 Ti 0.01 O2 is used as the positive electrode and metallic sodium is used as the negative electrode to assemble the NM-L10CT / NZSP / Na solid-state sodium battery. The battery assembly is carried out in a glove box under argon protection, and the oxygen and moisture content is <1 ppm.

Citation Information

Patent Citations

  • Quaternary sodium ion battery positive electrode material and sodium ion battery comprising same

    CN115583672A

  • Li &lt; + &gt;-substituted sodium ion battery positive electrode material as well as preparation method and application thereof

    CN116093305A

  • High-voltage sodium ion battery positive electrode material and application thereof

    CN118053993A

  • Method for producing lithium battery anode material doped with multi-elements by secondary depositing method

    CN1982219A

  • Air and moisture stable high-capacity positive electrode materials for sodium-ion battery

    WO2024161411A1